2017
DOI: 10.19082/5487
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrofluoric acid surface treatments on micro-shear bond strength of CAD/CAM ceramics

Abstract: IntroductionDental ceramics are appreciated as highly esthetic restorative materials that can simulate the appearance of natural dentition better than other materials. The aim of this study was to evaluate the effect of hydrofluoric acid concentration and etching time on micro-shear bond strength (μSBS) to IPS e.max CAD and Vita Mark II of a dual cured resin cement (Panavia F2.0).MethodsThis study was an experimental in vitro study, performed in the dental material research center of Babol University of Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 22 publications
3
17
0
5
Order By: Relevance
“…20 Er,Cr:YSGG laser with a wavelength of 2.78 µm has been used for surface roughening of different CAD/ CAM materials in the literature. [21][22][23] According to Kirmali et al, 24 when roughening the composite surfaces with 1.5-W, 2-W, and 3-W Er,Cr:YSGG laser irradiation, rough and irregular surfaces occur and acceptable shear bond strength similar to sandblasting is obtained. Barutcigil et al 23 also reported a mean SBS of 9.137 MPa for Er,Cr:YSGG laserirradiated Vita Enamic specimens at 2 W. According to the same study, this result was found to be similar to those obtained from CoJet sandblasting, 50-µm Al 2 O 3 sandblasting, and 10% HF acid etching surface treatments.…”
Section: Discussionmentioning
confidence: 99%
“…20 Er,Cr:YSGG laser with a wavelength of 2.78 µm has been used for surface roughening of different CAD/ CAM materials in the literature. [21][22][23] According to Kirmali et al, 24 when roughening the composite surfaces with 1.5-W, 2-W, and 3-W Er,Cr:YSGG laser irradiation, rough and irregular surfaces occur and acceptable shear bond strength similar to sandblasting is obtained. Barutcigil et al 23 also reported a mean SBS of 9.137 MPa for Er,Cr:YSGG laserirradiated Vita Enamic specimens at 2 W. According to the same study, this result was found to be similar to those obtained from CoJet sandblasting, 50-µm Al 2 O 3 sandblasting, and 10% HF acid etching surface treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Another study, evaluated different HF acid concentrations (9, 5, and 4%) in leucitereinforced feldspathic ceramic, and according to the authors, the HF concentration had no influence on the ceramic bond strength 19 . Other studies 26,27 evaluated the effect of HF concentrations (5 and 10%) and etching time in feldspar ceramic. According to these authors, the time and the concentration of HF had no influence on the ceramic bond strength as in the results of the present study.…”
Section: Qualitative Surface Topography Analysis (Sem)mentioning
confidence: 99%
“…The HF concentration and the ideal etching time should be adjusted for each type of ceramic to achieve optimal bond strength. 27 The second hypothesis that longer etching time (120s) promotes higher bond strength was not accepted. The 20-or 120-s etching time had no influence on bond strength values.…”
Section: Qualitative Surface Topography Analysis (Sem)mentioning
confidence: 99%
“…For restorations with glass-ceramic and success bonding with composite resin cements, the use of hydrofluoridric acid (HF) etching is recommended 30,31 . HF modifies the ceramic surface, because the acid removes the glassy matrix, exposes crystalline structure 12,32 , increases the roughness 11 and surface energy 13 in acidsensitive ceramics, as lithium disilicate 33 , forming hexafluorosilicates 34 .…”
Section: Discussionmentioning
confidence: 99%
“…HF acid 5% and 10% are the most usual acids used to change the surface ceramics 35 . The producer of IPS e.max CAD 36 suggests hydrofluoridric acid 5% etching during 20 seconds, but a new study shows that no difference between HF acid 10% and 5% in the same time 37 and, for micro-shear bond, HF 10% is higher when compared with the HF 5% 34 . Furthermore, hydrofluoridric acid 5% etching does not remove enough glassy matrix of lithium disilicate to increase the micromechanical retention of the resin cement in the ceramic surface; in contrast, the HF 10% removes 35 .…”
Section: Discussionmentioning
confidence: 99%